Attitude of Teachers and Students towards Online Examination during the COVID-19 period: A Study - Bora, Monjusree (Indian Journal of Educational Technology, 2024)
Covid-19 pandemic had paused our day-to-day life for a while when the whole world was shuttered by its devastation. For every country, the economy and education have remained the utmost priorities in matters of development. It is of no exception for our country that the most prominent sectors affected by Covid-19 were the economy and education. The most vulnerable was the student community because the offline classes were stopped and its related issues. Due to this, the mode of examination was online only. Several kinds of problems came to the forefront while analysing the advantages and disadvantages of online examination. The present study attempts to know the attitude of students and teachers towards online examinations. The investigator, by using a purposive sampling method, selected 256 undergraduate students and 80 teachers from different colleges in the Nagaon district of Assam. The data were analyzed by using a simple frequency percentage, Mean, and SD.